The other guest - Cooper, Helen (Helen Mary), 1985- (G. P. Putnam's Sons, 2022)
"After a shocking death at a luxurious Italian resort, two very different women must question everything-and everyone-they love in order to untangle truth from lies in this twisty, captivating read"--